Sleep stage sequence analysis of sleep onset REM periods in the hypersomnias. Issue 2 (20th October 2012) - Drakatos, Panagis; Suri, Angula; Higgins, Sean E; Ebrahim, Irshaad O; Muza, Rexford T; Kosky, Christopher A; Williams, Adrian J; Leschziner, Guy D
Abstract : Background: The Multiple Sleep Latency Test (MSLT) remains an important diagnostic tool in the diagnosis of hypersomnias. However, a positive MSLT may be found in other sleep disorders, such as behaviourally induced inadequate sleep syndrome (BIISS). It has been demonstrated that in sleep onset rapid eye movement (SOREM) periods in BIISS, REM sleep tends to arise from stage 2 sleep (non-REM (NREM) 2), rather than stage 1 sleep (NREM1), as in narcolepsy. Methods: We performed sleep stage sequence analysis on 127 patients with nocturnal polysomnography and MSLT, including 25 with narcolepsy with cataplexy (N+C), 41 with narcolepsy without cataplexy (N−C), 21 with idiopathic hypersomnia with long sleep time (IHL), 20 with BIISS and 20 with periodic limb movement disorder (PLMD). 537 naps were recorded, containing 176 SOREM periods. Results: All SOREM periods in the IHL, BIISS and PLMD groups arose from NREM2 sleep, 75% of those in N+C arose from NREM1 and in N−C only 52% arose from NREM1. Within the N−C group, those with SOREM periods all arising from stage 1 had a shorter MSL (p=0.02). Conclusions: These results suggest that SOREM periods arising from NREM1 have high sensitivity for the diagnosis of narcolepsy and that SOREM periods from NREM1 are a marker of severity, either of sleepiness or REM instability. Sleep stage sequence analysis of SOREM periods may also aid more accurate phenotyping of the hypersomnias and in particular clarify heterogeneity among patients with narcolepsy without cataplexy.